Combined use of Campath and total skin electron beam irradiation in mycosis fungoides - V. A. Doronin; Y. A. Krivolapov; A. V. Nechesnyuk; A. V. Pivnik (Онкогематология, 2022)
This article demonstrates case report and review of literature of successful use Campath in combination with total skin electron beam irradiation in mycosis fungoides.